IMPLEMENTASI E-KEUANGAN : PENYUSUNAN LAPORAN KEUANGAN DI PEMERINTAHAN KABUPATEN TEMANGGUNG - SARI, SHAFA EDITYA KARTIKA; PANGGIARTI, ENDANG KARTINI; SUNANINGSIH, SUCI NASEHATI (UNIKA Santo Thomas, 2022)
This research aims to convey an illustration of how the implementation of the process of preparing financial statements in Temanggung Regency compiled by BPKPAD and knowing what are the problems it is facing. The problems faced are related to the level of regional device work units (SKPD) that are late in the submission of SKPD financial statements to BPKPAD. with the problems that arise, it will affect the work process on BPKPAD such as delays during the realization of consolidated reports. The method used in this study is a case study using a type of qualitative method. This research object unit is at the Financial Management, Investment and Regional Assets Agency (BPKPAD) of Temanggung Regency. The results showed that BPKPAD Temanggung Regency uses the E-Financial software system in the preparation of consolidated financial statements.